2015
DOI: 10.1111/1467-8551.12131
|View full text |Cite
|
Sign up to set email alerts
|

Managing Nationality Diversity: The Interactive Effect of Leaders’ Cultural Intelligence and Task Interdependence

Abstract: In light of the workforce's increasing nationality diversity, our study explores the antecedents for the successful management of nationality diversity as visualized in a favourable diversity climate and enhanced team performance. We propose a doublecontingency model in which we argue that the effects of nationality diversity will be dependent upon task interdependence and leaders' cultural intelligence. We propose that nationality diversity will be more consequential in more interdependent teams, in which tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 76 publications
(149 reference statements)
2
30
0
Order By: Relevance
“…Insert Table 5 about here CQ has been found to be an important moderator in various contexts, including expatriation (Froese, Kim, & Eng, 2016), business travel (Ramsey, Leonel, Gomes, & Monteiro, 2011), education (Jie & Harms, 2017), export (Magnusson, Westjohn, Semenov, Randrianasolo, & Zdravkovic, 2013), international study (Presbitero, 2016b;Volpone, Marquardt, Casper, & Avery, 2018), intercultural service encounters (Lorenz, Ramsey, Tariq, & Morrell, 2017), and intercultural teamwork (Rosenauer, Homan, Horstmeier, & Voelpel, 2016). In general, CQ strengthens the relationship between intercultural differences and cross-cultural adjustment and performance (Lorenz et al, 2017;Magnusson et al, 2013;Rosenauer et al, 2016) and diminishes the relationship between such differences and adaption problems as strain (Ramsey et al, 2011). For example, Rosenauer et al (2016) found that teams with higher national diversity have a better performance only when team leaders' CQ and task interdependence are high.…”
Section: Moderating Effects Of Cultural Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…Insert Table 5 about here CQ has been found to be an important moderator in various contexts, including expatriation (Froese, Kim, & Eng, 2016), business travel (Ramsey, Leonel, Gomes, & Monteiro, 2011), education (Jie & Harms, 2017), export (Magnusson, Westjohn, Semenov, Randrianasolo, & Zdravkovic, 2013), international study (Presbitero, 2016b;Volpone, Marquardt, Casper, & Avery, 2018), intercultural service encounters (Lorenz, Ramsey, Tariq, & Morrell, 2017), and intercultural teamwork (Rosenauer, Homan, Horstmeier, & Voelpel, 2016). In general, CQ strengthens the relationship between intercultural differences and cross-cultural adjustment and performance (Lorenz et al, 2017;Magnusson et al, 2013;Rosenauer et al, 2016) and diminishes the relationship between such differences and adaption problems as strain (Ramsey et al, 2011). For example, Rosenauer et al (2016) found that teams with higher national diversity have a better performance only when team leaders' CQ and task interdependence are high.…”
Section: Moderating Effects Of Cultural Intelligencementioning
confidence: 99%
“…In general, CQ strengthens the relationship between intercultural differences and cross-cultural adjustment and performance (Lorenz et al, 2017;Magnusson et al, 2013;Rosenauer et al, 2016) and diminishes the relationship between such differences and adaption problems as strain (Ramsey et al, 2011). For example, Rosenauer et al (2016) found that teams with higher national diversity have a better performance only when team leaders' CQ and task interdependence are high. Among the four aspects of CQ, metacognitive CQ is the dimension that most frequently shows statistically significant moderating effects, while motivational CQ seems to be the least important moderator.…”
Section: Moderating Effects Of Cultural Intelligencementioning
confidence: 99%
“…These scores can then be used to improve empirical studies, which must determine whether it is the individual CQ or an aggregated score for the group or a dyad that explains business outcomes. Researchers can explore whether and how CQ on different levels moderates the relationships between nationality and diversity effects (Rosenauer et al, 2016).…”
Section: Collective Cq Gm or Cc: Future Research From A Macro Perspmentioning
confidence: 99%
“…CQ can affect multiple facets of virtual work, including team member satisfaction, role clarity, trust, communication, and performance (Henderson, Stackman & Lindekilde, 2018;Moon, 2013;Presbitero, 2016). It is imperative that the leaders of GVTs be high in CQ because they will shape the team's diversity environment perceptions (Rosenauer, Homan, Horstmeier & Voelpel, 2016). Almost one quarter (23%) of respondents in CultureWizards (2016) survey of GVTs, say their virtual teams fail to capitalize on their cultural diversity.…”
Section: Importance Of Cq For Gvtsmentioning
confidence: 99%
“…People that wish to lead a GVT should receive professional training to e-leaders that pays special attention to CQ-motivation could empower leaders to be aware of and supportive towards their team members cultural diversity (Henderson et al, 2018). Studies suggest that for managing culturally diverse teams the leaders are critical for their management and organizations should provide CQ training programs to enhance the leader's capabilities (Rosenauer et al, 2016).…”
Section: Strategies Of Cq Leadershipmentioning
confidence: 99%